Effect of Notoginsenoside R1 on reparative dentin formation via regulating the function of human dental pulp stem cells - Xuan He; Dan Liang; Xinyi Zhao; Kaixin Liu; Zicheng Zhang; Meiling Li; Xuemeng Ma; Wenxia Chen; Xiaoyi Zhong (Tissue and Cell, 2027)

Liensinine can improve vascular remodeling in hypertension through the ferroptosis-related TLR4 inflammatory pathway - Daxin Chen; Peizhi Jia; Meiling Wang; Baojie Du; Haitao Du; Xi Huang; Jianwei Zeng; Qiaoyan Cai; Ling Zhang; Ying Zhu; Shan Lin; Dawei Lian; et al. (Journal of Molecular Medicine, 2026)

Tricholoma matsutake polysaccharides promote physiological germination and metabolic reactivation of Bacillus cereus spores: Mechanisms and application in milk preservation - Meiling Zhao; Yujie Zhong; Yanjie Chen; Zhijia Liu; Chuanqi Chu; Qingyun Wang; Xiaoxia Zhao; Tao Wang; Junjie Yi (International Journal of Food Microbiology, 2026)

Experimental study on active local flexural strengthening of reinforced concrete beams using near-surface-mounted NiTiNb shape memory alloy wires for wet-joint repair - Jichong Wang; Shengshan Pan; Yuanmeng Chen; Hui Qin; Meiling Hu; Bing Chen (Engineering Structures, 2026)

A natural special-shaped MXene/bamboo evaporator with synergistic hydrothermal management for solar water purification - Jinhong He; Zongpei Zhang; Tianqing Shu; Weisheng Yang; Xiaoxu Ma; Jingren Ma; Meiling Chen; Fengshan Zhang; Guigan Fang; Huining Xiao; Jingquan Han (Desalination, 2026)

Oxygen-adaptive continuous lactate monitoring via dual-regime electrochemical sensing and dynamic calibration strategy - Xinyi Wang; Yuying Lin; Rubing Xiong; Jing Liu; Yue Liu; Zijie Li; Yongmei Chen; Yong Xia; Zhiqi Li; Lei Mou; Meiling Liu (Analytica Chimica Acta, 2026)

Zeolitic imidazolate framework enabled heat-resistant enzymatic biosensor for real-time and non-invasive detection of glucose - Qingwen Zhang; Meiling Yuan; Jingwen Chen; Ying Yang; Meng Lu; Chaoyue Cui; Xiaohu Liu; Hu Chen; Yi Wang (Chemical Engineering Journal, 2026)

A double-platform assay for rapid and on-site detection of chikungunya virus by integrating catalytic hairpin assembly with lateral flow immunochromatography assay - Ruijie Lu; Dawen Chen; Ai Chen; Shuo Ma; Yuming Yao; Yaya Chen; Gulinaizhaer Abudushalamu; Meiling Zhou; Xiao Li; Yue Zheng; Wenjing Lu; Yueqi Wang; et al. (Analytica Chimica Acta, 2026)

Rapid Detection of Spring Viremia of Carp Virus ( SVCV ) Using RAA ‐ CRISPR /Cas12a - Xiaoyang Li; Aoqing Zhang; Yingying Li; Yingying Wang; Hao Zheng; Defeng Zhang; Yan Ren; Xubing Mo; Yuting Deng; Junyu Luo; Meiling Yu; Bo Chen; et al. (Journal of Fish Diseases, 2026)
Spring viremia of carp virus (SVCV), that can infect cyprinoid and koi causing an acute hemorrhagic symptom, with a feature of widespread epidemic, which poses a severe threat to the global aquaculture industry. Given the absence of specific effective medicine or vaccines, the early, accurate diagnosis is critical in the disease prevention. Many SVCV detection methods have been established, but most require specialized equipment and skilled operators, which limits their field application. In this study, we established a recombinase‐mediated isothermal amplification (RAA) in conjunction with the CRISPR/Cas12a system targeting the screened conserved region of the G gene in the genome to identify SVCV. The optimal combination of the primer pairs and crRNA was screened via the fluorescence intensity. In addition, the test exhibited high sensitivity and specificity, which could detect at the limit of 1.243 × 10 1 copies/μL and show no cross‐reactivity with other common freshwater fish pathogens. Furthermore, the result could be visible by excitation of fluorophores by blue light at 39°C within 30 min. The integrated method combines the advantages of RAA and CRISPR‐based signal transduction, offering a diagnosis project in resource‐limited aquaculture environments and a field‐applicable early warning of SVCV.

Genome-wide characterization of terpene synthase genes in Ginkgo biloba and their regulatory role in terpene trilactones biosynthesis - Ang Xu; Chenglin Luo; Chunxia Chen; Yumeng Gao; Wenjing Qin; Qi Wang; Lisha Shi; Xiaoming Yang; Meiling Ming; Fuliang Cao; Fangfang Fu (Plant Science, 2026)

Forecasting transportation decarbonization pathways and deciphering structural moderating mechanisms in in-situ urbanization: An interpretable machine learning and multi-scenario assessment framework - Lu Chen; Wei Liu; Meiling Wu; Jingyi Zhao; Fanjie Luo (Environmental Impact Assessment Review, 2026)

Inner Ear Organoids: Recent Progress and Challenges - Yingxinyu Li; Cairong He; Jiayan Liu; Haiqin Zhang; Hongxia Zhang; Zheyu He; Mengyang He; Meiling Chen; Feiyan Zhou; Jie Ding (Stem Cell Reviews and Reports, 2026)

Sophoraflavanone G disrupts human sperm function via impairing CatSper-mediated Ca2+ signaling - Meiling Yang; Ze Xu; Jiali Zhang; Nanxi Ji; Jieling Huang; Yiling Lu; Chunli Sha; Sijie Gaoliu; Xuhui Zeng; Hang Kang; Liping Chen (Reproductive Toxicology, 2026)

Impact of Fly Ash on the CO2 Mineralization Efficiency and Interfacial Transition Zone Properties of Sustainable Coal Gangue-based Materials - Lei Qin; Feilong Zhang; Zitong Xue; Hui Wang; Miao Mu; Meiling Xiong; Niandong Chen (Water, Air, & Soil Pollution, 2026)

Regional climate downscaling simulations for China since the Last Glacial Maximum - Naixin Cao; Liang Ning; Jian Liu; Zhengyu Liu; Mi Yan; Weiyi Sun; Meiling Jiang; Xueyuan Kuang; Huayu Lu; Kefan Chen; Yanmin Qin; Qin Wen; et al. (Science China Earth Sciences, 2026)

Organophosphate flame retardants and immunotoxicity: An integrated bibliometric and systematic review of epidemiological and mechanistic evidence - Chengyue Ma; Yuhao Zhong; Xiaowen Huang; Minghui Li; Jinsong Zhao; Chunji Wang; Fang Zhang; Yue Jia; Yuxin Jiang; Yingli Li; Meiling Shi; Shuqi Chen; et al. (Journal of Environmental Sciences, 2026)

Bionic construction and performance assessment of 3D bioprinted small-diameter artificial blood vessels - Yuan-Zhu Xin; Wenyu Jin; Qianqian Wu; JunHee Lee; Geng Li; Yan Chen; Jun Liu; Seok-Jo Yang; Jiazi Gao; Meiling Quan; Zhenning Liu (Chemical Engineering Journal, 2026)

Genome-wide analysis of the papaya bZIP gene family identifies CpbZIP52 as a key regulator of fruit postharvest ripening - Meiling Ding; Shanni Cao; Meng Zeng; Min Zhang; Hongya Tang; Xiaochun Chen; Xianqi Fu; Sicheng Bai; Min Yang; Kaidong Liu (Plant Science, 2026)

Effects of nodule geometry on collection performance and structural improvement of a rotary-rake collector for deep-sea mining - Qiang Yang; Zekun Chen; Junlan Deng; Meiling Liu; Jianxin Xia; Dingbang Wei (Ocean Engineering, 2026)

Facet and crystallinity-dependent transformation of lepidocrocite impacts cadmium redistribution - Meiling Yin; Jin Wang; Songxiong Zhong; Xiaofei Li; Fei Huang; Chen Yang; Fangbai Li; Zhi Dang; Chuling Guo (Environmental Pollution, 2026)

Preliminary study on targeted therapy of breast cancer using tumor cell membrane-coated dual-loaded liposomes based on chemo-photothermal synergistic effects - Yuwei Wang; Shuchao Pang; Yun Lu; Xialin Guo; Chanlian Li; Meiling Chen; Xiaoliang Ren (Drug Delivery and Translational Research, 2026)

Drug-Induced Noninfectious Myocarditis/Pericarditis: A Real-World Pharmacovigilance Study Using the FAERS Database - Shijie Zhao; Weiyi Chen; Chao Tao; Ke Wang; Liuxuan Yang; Ruixiao Li; Meiling Zhou; Jinlu Shang; Xianbin Liu (Cardiovascular Toxicology, 2026)

Spatiotemporal Profiling of Intratumoral Free Payload Distribution via MALDI Imaging Mass Spectrometry: Implications for Drug-to-Antibody Ratio Optimization in Antibody–Drug Conjugates - Tingting Cai; Ziyi Li; Qiaofang Yan; Guangcun Huang; Kaiying Jia; Xiaotong Chen; Junling Dun; Jinghua Zou; Meiling Tan; Yue Wu; Fan Wang (The AAPS Journal, 2026)

Community characteristics and risks of disinfection residual bacteria (DRB) during intermittent chlorination of stored rainwater - Zhiwen Chen; Xiaobin Liao; Binxiong Hu; Ye Yang; Meiling Liu; Yingying Dong; Tao Li; Likun Lv; Mawuli Dzakpasu; Yuefeng Xie; Wendong Wang (Journal of Environmental Chemical Engineering, 2026)

Bridging data gaps in landslide early warning: Physics-derived rainfall thresholds under rainfall uncertainty - Hao Zou; Weiye Huang; Ting Liu; Henghao Cai; Shuai Mao; Bing Chen; Meiling Wu; Qingyu Zhang; Xiao Liu; Shu Zhang (Engineering Geology, 2026)

Tracing thallium pollution in arsenic mining/smelting areas using high-precision thallium isotopic composition - Xudong Wei; Shunlong Jiang; Jin Wang; Hangfei Guo; Dieyu Chen; Ke Lin; Meiling Yin; Wanpeng Chen; Yinyin Lu; Yurong Gao; Juan Liu (Applied Geochemistry, 2026)

Iron single-atom/cluster nanozyme with enhanced oxidase-like activity for fluorescent/colorimetric analysis of Total antioxidant capacity in food - Meiling Chen; Yongmin Lei; Junlin Liu; Qiming Liu; Xingjian Song; Ting He; Guo-jun Zhang; Yujie Sun; Yulin Zhang; Yuqing Qin; Shaowei Chen (Food Chemistry, 2026)

Digital Expansion: Pathways for a Digital Ecology to Empower Water Resource Carrying Capacity - Dongming Gu; Xiaofei Hu; Meiling Chen; Yunjie Xie (Water Resources Management, 2026)

Bibliometric analysis of Pseudomonas aeruginosa vaccine development highlighting research status, evolution, and future opportunities - Shiqin Huang; Yi Zhou; Meiling Wu; Xinyan He; Jie Liu; Xinyao Chen; Chunyong Xia; Wen Wu; Ying Fan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

The changes of antioxidant system, membrane integrity and phenolics metabolism participate in bongkrekic acid and adenosine triphosphate-mediated energy status regulating longan pericarp browning - Meiling Li; Hetong Lin; Ruiling Zhuo; Boqiang Li; Yifen Lin; Yihui Chen; Zhongqi Fan; Hui Wang (Postharvest Biology and Technology, 2026)

Predicting ecological risks of heavy metals in watersheds based on interpretable machine learning models: under the framework of data scarcity - Hong Chen; Meiling Kong; Zhenghua Wu; Liu Gong; Lanlan Huang; Yihan Li; Fazhi Xie (Environmental Monitoring and Assessment, 2026)

Underwater Noise in Offshore Wind Farms: Monitoring Technologies, Acoustic Characteristics, and Long-Term Adaptive Management - Peibin Zhu; Zhenquan Hu; Haoting Li; Meiling Dai; Jiali Chen; Zhuanqiong Hu; Xiaomei Xu (Journal of Marine Science and Engineering, 2026)
The rapid global expansion of offshore wind energy (OWE) has established it as a critical component of the renewable energy transition; however, this development concurrently introduces significant underwater noise pollution into marine ecosystems. This paper provides a comprehensive review of the acoustic footprint of OWE across its entire lifecycle, rigorously distinguishing between the high-intensity, acute impulsive noise generated during pile-driving construction and the chronic, low-frequency continuous noise associated with decades-long turbine operation. We critically evaluate the engineering capabilities and limitations of current underwater acoustic monitoring architectures, including buoy-based real-time monitoring nodes, cabled high-bandwidth systems (e.g., cabled hydrophone arrays with DAQ/DSP and fiber-optic distributed acoustic sensing, DAS), and autonomous seabed archival recorders (PAM deployment). Furthermore, documented biological impacts are synthesized across diverse taxa, ranging from auditory masking and threshold shifts in marine mammals to the often-overlooked sensitivity of invertebrates and fish to particle motion—a key metric frequently missing from standard pressure-based assessments. Our analysis identifies a fundamental gap in current governance paradigms, which disproportionately prioritize the mitigation of short-term acute impacts while neglecting the cumulative ecological risks of long-term operational noise. This review synthesizes recent evidence on chronic operational noise and outlines a conceptual pathway from event-based compliance monitoring toward long-term, adaptive soundscape management. We propose the implementation of integrated, adaptive acoustic monitoring networks capable of quantifying cumulative noise exposure and informing real-time mitigation strategies. Such a paradigm shift is essential for optimizing mitigation technologies and ensuring the sustainable coexistence of marine renewable energy development and marine biodiversity.

An Ultrasensitive 1,2,3-Triazole Schiff-Based Fluorescence Probe for the Detection of Al3+ and Developing Application of Biological Activity - Chunyang Liu; Junfeng Chen; Xun Kang; Meiling Le; Huajie J. Feng; Wenying Y. He (Journal of Fluorescence, 2026)

Divergent responses of water use efficiency to drought events in planted forests: Southern vs Northern China - Zipeng Gu; Xingwei Chen; Huaxia Yao; Jiefeng Wu; Meiling Zheng; Wenjun Gu; Senzhen Wang (Journal of Hydrology, 2026)

Effectiveness and mechanism of in situ sludge biochar carrier enhancing salt-tolerant bacteria for pyrazolone degradation in high-salinity pharmaceutical wastewater - Yuying Ma; Zheyu Chen; Genping Yi; Ezzat H Elshazly; Qingshan Liu; Hongyan Zhang; Meiling Zheng; Aijie Wang; Wenzong Liu (Bioresource Technology, 2026)

Genetic context-dependent regulation of FlbE enhances morphology modulation and citric acid production in Aspergillus niger - Meiling Chen; Xiaomei Zheng; Peng Du; Xiaomeng Ni; Zhimin Li; Ping Zheng; Jibin Sun (Bioresource Technology, 2026)

Optimal information transmission in a non-Markovian auto-regulatory gene expression system - Zihao Wang; Meiling Chen; Zhenquan Zhang; Xiyan Yang; Tianshou Zhou; Changhong Shi; Jiajun Zhang (BioSystems, 2026)

Tetrahydrocurcumin for Major Depressive Disorder with Therapeutic Potential and Mechanistic Insights from Clinical and Preclinical Studies - Ying Guo; Jianping Xie; Haiyun Luo; Yun Yuan; Fang Long; Jingyuan Meng; Hui Tan; Yuanping Li; Bibo Cai; Meiling Chen; Liyan Yang; Jingmei Zhong; et al. (Molecular Neurobiology, 2026)

Spatiotemporal changes of soil organic carbon in intensive croplands over three decades: Emerging role of farmland utilization shifts - Mingtao Xiang; Xiaojia Chen; Songchao Chen; Chunyan Wu; Meiling Sheng; Zhouqiao Ren; Wanzhu Ma; Ming Ming; Xunfei Deng; Yu Zhan (Soil and Tillage Research, 2025)

Unveiling the seasonal variations in greenhouse gas emissions from a representative full-scale swine farm’s wastewater treatment system via life cycle assessment - Xingyun Yuan; Meiling Lu; Zhiyin Wu; Zixuan Liu; Xin Wen; Baohua Ma; Yongde Zou; Tao Chen; Yinbao Wu (Process Safety and Environmental Protection, 2025)

Monsoonal intensity dominated the Eocene evolution of paleovegetation and paleoclimate in northern South China Sea - Jinhua Zeng; Tao Jiang; Keqiang Wu; Desheng Hu; Yong Man; Licheng Cao; Cong Cheng; Zigui Chen; Kun Wang; Nan Bai; Meiling Feng; Ziyi Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Numerical simulation of wind field characteristics and enhanced heat exchange performance for the novel bucket-shaped anti-frosting evaporator - Guodong Qiu; Meiling Huang; Dan Liu; Yanfeng Chen; Weihua Cai (International Journal of Refrigeration, 2025)

Visible light driven highly selective oxidation of HMF coupled with H2 evolution via bimetal-doped synergism on ZnIn2S4 nanosheets - Yachen Hu; Wei Jiang; Zijun Zhang; Qinqin Jiang; Yawen Jiang; Lang Sun; Panjing Xu; Yanling Chang; Chuanqiang Wu; Ziming Fan; Meiling Wang; Zhou Chen; et al. (Chemical Engineering Journal, 2025)

Laser-engineered rattan evaporators for scalable and sustainable solar desalination - Haocheng Xu; Yingpeng Liu; Pei Qi Woon; Meiling Chen; Xinwu Xu; Bofan Li (Chemical Engineering Journal, 2025)

Patterns and Influencing Mechanism of Plant Species Richness of Carex-dominated Wetlands in China - Jingci Meng; Guodong Wang; Yue Guo; Meiling Zhao; Nanlin Hu; Yusong Yuan; Yantong Zhao; Qi Chen; Zhibin Ren; Bo Liu; Ming Jiang (Chinese Geographical Science, 2025)

AKR1B1 is Required for Maintaining Acute Leukemia Cell Survival by Epigenetic Silencing of Tumor Suppressor Genes - Jingyu Chen; Lu Xu; Wangshi Li; Meiling Sun; Yao Chen; Ting Qiu; Yue Wu; Xingzhi Lv; Fukai Liu; Huitao Fan (Biochemical Genetics, 2025)

A novel “WRF+AutoML” framework for enhanced heat estimation in urban environments - Meiling Gao; Huifang Li; Fei Chen; Mengzi Zhou; Guijun Yang; Dun Zhu; Dawei Han; Zhenhong Li (Sustainable Cities and Society, 2025)

Possible influences of tropical vegetation shift on the glacial-interglacial temperature changes - Liping Tian; Cong Chen; Mengyuan Wang; Chuanxiu Luo; Xiao Zhang; Yanming Ruan; Jiantao Cao; Meiling Man; Zhuo Zheng; Xiaoqiang Yang; Kangyou Huang; Li Li; et al. (Global and Planetary Change, 2025)

Sequential temperature design in high-speed railway stations: A dynamic thermal strategy balancing thermal comfort and energy efficiency - Ye Yuan; Meiling Li; Junxi Gao; Gang Liu; Zongwu Xu; Ying Chen; Hanyuan Zhang (Building and Environment, 2025)

Wheat yield prediction using an enhanced WOFOST with soil stratified hydrothermal module driven by GLASS and ERA5-land products over Yellow River Basin - Jing Zhang; Guijun Yang; Meiling Gao; Lijie Zhang; Weinan Chen; Miao Liu; Youming Zhang; Aohua Tang; Zhenhong Li (Computers and Electronics in Agriculture, 2025)

DNP and ATP regulate disease progression in Neopestalotiopsis clavispora-infected guava fruit by modulating respiratory and energy metabolism - Hongbin Chen; Yifei Chen; Xuanjing Jiang; Yuzhao Lin; Yazhen Chen; Meiling Li; Yihui Chen (Postharvest Biology and Technology, 2025)

Graft−growth of Cobalt−based Prussian blue analogs on bamboo for indoor formaldehyde removal - Yi Zhu; Honghui Yan; Ruiqi Xin; Yuding Zhu; Miaomiao Zheng; Xiangxing Wu; Yiting Zhang; Ting Wang; Meiling Chen; Song Li; Jeonghun Kim; Wenkai Zhu (Environmental Research, 2025)

Diverse paths of green building development from a stakeholder collaboration perspective - Dongming Gu; Xiaofei Hu; Jianing Zhang; Meiling Chen (Energy and Buildings, 2025)

The intergrowth of YTa7O19 in L-Ta2O5 with Er3+/Yb3+ enhancing pure green upconversion luminescence intensity by molten salt synthesis - Yuhan Fan; Yongze Cao; Zhihua Zhang; Hualong Tao; Meiling Li; Xizhen Zhang; Sai Xu; Baojiu Chen (Chemical Engineering Journal, 2025)

CO2 adsorption and separation properties of decorative paper impregnated with amino-functionalized cellulose nanofibers/waterborne acrylic resin - Xiaopin Bu; Qian Wei; Zhuoxin Liao; Yuding Zhu; Meiling Chen; Junhui Yang; Xiuzhen Lin; Donggyun Kim; Xiangyu Wang; Song Li; Jeonghun Kim; Wenkai Zhu (Chemical Engineering Journal, 2025)

Spatiotemporal variation of forest water conservation based on dual-variable calibration of runoff and evapotranspiration with SWAT model - Jiao Chen; Meiling Zheng; Feng Lin; Xingwei Chen; Huaxia Yao (Agricultural and Forest Meteorology, 2025)

Consumer preference of new energy vehicles and regional heterogeneity in China: the role of emotion and region - Yuanyuan Wang; Jin-Hua Xu; Meiling Chen (Environment, Development and Sustainability, 2025)

Study on the evolution and prediction of carbon emission from land use change in Tulufan-Hami basin under the influence of urbanization and climate change - Meiling Huang; Yusuyunjiang Mamitimin; Abudukeyimu Abulizi; Rebiya Yimaer; Bahejiayinaer Tiemuerbieke; Han Chen; Tongtong Tao; Yunfei Ma (Environment, Development and Sustainability, 2025)

Different impacts of temperature and precipitation on vegetation net primary production of global marsh wetlands - Jiaqi Zhang; Meiling Zhao; Rong Ma; Mingming Feng; Chen Ding; Liyuan Wu; Xianguo Lu; Xiangjin Shen; Ming Jiang (Global and Planetary Change, 2025)

Tamoxifen regulates ferroptosis of hepatocytes by targeting SLC1A5 to activate hepatic stellate cells and liver fibrosis - Sha Shi; Meiling Zhang; Chengkai Zhu; Shanhao Zhu; Jie Yu; Qi Sui; Jiaqi Xu; Juan Ren; Jingnan Zhang; Peng Chen; Yi Zhang (Chemico-Biological Interactions, 2025)

Comparison of Meltpro Myco Assay with MALDI-TOF Mass Spectrometry for rapid and accurate detection of clinical Mycobacterium Species - Kehao Peng; Liuyue Xu; Xuezhi Wang; Jianming Hong; Gengchen Zhang; Yuchuan Zhao; Yinong Ye; Zengqi Huang; Jinmei Zhang; Yuchun Huang; Zhiqiao Wu; Xiaolin Yu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Spatial distribution and risk assessment of microplastics in surface sediments in semi-enclosed waters: a case study of Laizhou Bay - Xuzhen Zhang; Hongxian Chu; Meiling Yin; Yadong Liu; Peng Chen; Qiangqiang Zhang; Xuejian Dai; Linghao Kong (Frontiers in Marine Science, 2025)
Marine ecosystems are the most important sinks for microplastics (MPs) from inland sources, and the input of large quantities of MPs into the oceans poses a serious threat to marine organisms and ecosystems. However, the characteristics of MPs contamination and its risk in semi-enclosed seas remain poorly understood. In this research, we conducted a comprehensive analysis and evaluation of the distribution patterns and ecological risks related to MPs found in the surface sediments of Laizhou Bay. We gathered surface sediments from various locations within the bay, which were then processed and analyzed to assess the MP content. According to the results, MPs in Laizhou Bay were widely distributed, with abundances ranging from 36–2125.5 items/g d.w. at different points, with an average of 534.7 items/g d.w. The MP forms were mainly fragments (61.91%) and particles (37.45%), with polyamide (PA) (32.73%), polyethylene terephthalate (PET) (12.42%), and polyurethane (PU) (10.81%) being the most dominant polymer types. MPs mainly originated from marine aquaculture, fishing, and domestic plastic waste; the contribution from marine activities was higher than that from land-based inputs, and their migration and dispersion were mainly affected by the hydrodynamics of water body exchange and intra-bay circulation. According to the pollution load index, the risk index of MPs in Laizhou Bay ranged from 1 to 7.68, indicating a low pollution level. However, the polymer risk index indicated that microplastic pollution in Laizhou Bay was at high risk, and PU and polyvinyl chloride were identified as the primary high-risk sources. This study systematically analyzed the composition, distribution, and multiple source characteristics of MPs in Laizhou Bay. The ecological risks associated with these MPs were assessed through the analysis of pollution load and polymer risk indices. This research offers a valuable dataset and a scientific foundation for understanding and managing MP pollution in semi-enclosed marine environments.

The behavior of NOM-Cu(Ⅱ)colloids at the goethite interface - Yuekang Chen; Lijuan Zeng; Kai Chen; Meiling Yin; Xiongkai Zheng; Yuting Zhou; Yanping Deng; Jiehong Ye; Zhi Dang; Chuling Guo (Water Research, 2025)

Comparative transcriptomic and metabolomic analyses reveal the role of acidic electrolyzed-oxidizing water in enhancing disease resistance in Phomopsis longanae Chi-infected longans - Meiling Li; Zhongqi Fan; Xiaoze Dai; Mengshi Lin; Yifen Lin; Hui Wang; Ruiling Zhuo; Yen-Con Hung; Hetong Lin; Yihui Chen (Postharvest Biology and Technology, 2025)

Surface engineering of copper peroxide nanodots and Au nanozyme on porphyrin-based metal-organic frameworks induces cascade reactions for colorectal cancer treatment - Haoyu Chen; Rong Liu; Jiaxin Fu; Xiaohan Zhang; Xiaohua Zhu; Mingjie Wei; Feng Liu; Peng Yin; Haitao Li; Youyu Zhang; Meiling Liu; Juewen Liu (Chemical Engineering Journal, 2025)

Breast Cancer Bone Metastasis: Novel Prognostic Biomarkers Identified - Meiling Chu; Yan Zhang; Jie Chen; Hui Cong; Yulian Yin; Hongfeng Chen (Phenomics, 2025)

Environment disturbances influence bacterial diversity, structure and co-occurrence network in the Digitaria sanguinalis rhizosphere - Yiming Dai; Ye Cui; Qingchen Xiao; Meiling Ping; Yiming Zhang; Shiguang Hu; Hao Chen; Xiaoyu Li; Jin Chen (Physiological and Molecular Plant Pathology, 2025)

Calcium isotope composition of the Gangdese continental arc deep crust and implications for making continental crust - Meiling Wang; Zaicong Wang; Liang Guo; Zongqi Zou; Fei Wu; Wei Dai; Jingliang Guo; Kang Chen; Lanping Feng; Haihong Chen; Ming Li; Yongsheng Liu (Geochimica et Cosmochimica Acta, 2025)

Three birds with one stone: a facile superparamagnetic aptasensor for selective capture, dual-mode detection and efficient elimination of methicillin-resistant Staphylococcus aureus - Fengfeng Zhao; Yuming Yao; Shuo Ma; Jiwei Wang; Abudushalamu GuliNaizhaer; Meiling Zhou; Yaya Chen; Xun Gao; Xiaobo Fan; Chen Zhang; Xinglu Jiang; Guoqiu Wu (Chemical Engineering Journal, 2025)

Confining PMo12 in flexible nanocages for enhanced electrochemical energy storage - Yuanyuan Yan; Chongji Wang; Yuhang Chen; Cao Wu; Kezhuo Xie; Zhenyu Liu; Tianyuan Zhang; Weifeng Liu; Xuguang Liu; Tian Wang; Zhaofeng Chen; Shengbo Sang; et al. (Chemical Engineering Journal, 2025)

Oxygen-containing functional groups of biochars enhancing the oxygen release of CaO2 and the generation of free radicals - Qiang Hu; Junheng Zhang; Yadi Pan; Kuan Ding; Chaoyang Xu; Jinyu Hou; Wuxing Liu; Chanchana Thanachayanont; Thipjak Na Lampang; Meiling Chen; Shu Zhang (Process Safety and Environmental Protection, 2025)

Pan-genome and haplotype map of cassava cultivars and wild ancestors provide insights into its adaptive evolution and domestication - Zhiqiang Xia; Zhenglin Du; Xincheng Zhou; Sirong Jiang; Tingting Zhu; Le Wang; Fei Chen; Luiz Carvalho; Meiling Zou; Luis Augusto Becerra Lopez-Lavalle; Xiaofei Zhang; Liangye Xu; et al. (Molecular Plant, 2025)

Altering wilting time and chopping length to optimize Medicago polymorpha L. fermentation ripening rate and flavour - Ning Mao; Hanyu Zhang; Ermei Du; Meiling Fan; Shihao Liu; Chaosheng Liao; Chao Chen; Hong Sun; Yulong Zheng; Ping Li; Yixiao Xie (Food Bioscience, 2025)

Development of the novel formulations of perospirone for the treatment of schizophrenia - Zijun Zhang; Famin Ke; Jili Wu; Xiyao Li; Xin Chen; Lanxing Zhang; Pei Jing; Zerong Liu; Zhongbing Liu; Ruilin Lu; Shihua Fu; Meiling Zhou; et al. (Drug Delivery and Translational Research, 2025)

Toxicokinetic insights into distinct mechanisms of action of two thyroid toxicants: Propylthiouracil and pregnenolone 16α‑carbonitrile - Naïs Clavel Rolland; Bénédicte Kiehr; Meiling Zhu; Chun Chen; Peng Gao; Thierry Pourcher; Olivier Blanck (Toxicology and Applied Pharmacology, 2025)

Copper oxide nanoparticles disrupt lysosomal function and promote foam cell formation in RAW264.7 macrophages - Yilin Luo; Kun Zhang; Lejiao Mao; Meiling Tan; Xiaomei Dong; Na Li; Yuexing Zhou; Chengzhi Chen; Zhen Zou; Jun Zhang (Toxicology, 2025)

RealFusion: A reliable deep learning-based spatiotemporal fusion framework for generating seamless fine-resolution imagery - Dizhou Guo; Zhenhong Li; Xu Gao; Meiling Gao; Chen Yu; Chenglong Zhang; Wenzhong Shi (Remote Sensing of Environment, 2025)

Rapid visual detection of glutathione in vegetables and distinguishing multiple sulfur-containing compounds by smartphone-assisted sensor based on calcined PPy@CuNi-ZIF-67 nanozyme with enhanced oxidase-like activity - Linchun Nie; Jiazhi Xia; Jiawei Liao; Na Liu; Meiling Xu; Dejing Meng; Wenjing Liu; Qingxiang Zhou; Chunmao Chen (Food Chemistry, 2025)

Divergent trends in vegetation greenness and resilience across China's forestry ecological engineering regions - Xinxin Fu; Zhenhong Li; Jiahao Ma; Meiling Zhou; Lili Chen; Jianbing Peng (Ecological Engineering, 2025)

Construction of site-specific immobilized lipase in bio-inspired “rigid and flexible” composite PVIm/ZIF-8 for long-cycle biodiesel synthesis from waste cooking oil - Qian Wang; Xinyuan Zheng; Meiling Ge; Rong Chen; Fangpei Ma; Jianming Pan; Fu Yang (Chemical Engineering Journal, 2025)

The design of novel lithium salt additives: 4-benzonitrile-1,3-double (trimethylboric acid) lithium (LBTA) to endow inherent superior stability in high voltage lithium ion batteries - Lucheng Li; Meiling Liu; Peng Yang; Wenfeng Yuan; Jun Chen (Chemical Engineering Journal, 2025)

Ecosystem resilience response to forest fragmentation in China: Thresholds identification - Xinxin Fu; Zhenhong Li; Jiahao Ma; Meiling Zhou; Lili Chen; Jianbing Peng (Journal of Environmental Management, 2025)

Sensitive measurement of polycyclic aromatic hydrocarbons based on strong enrichment from magnetic covalent organic framework before high performance liquid chromatography analysis - Guangyu Dong; Liushan Jiang; Linchun Nie; Jiawei Liao; Xiaodie Geng; Wenjing Liu; Dejing Meng; Meiling Xu; Na Liu; Qingxiang Zhou; Chunmao Chen (Journal of Environmental Chemical Engineering, 2025)

Multi-residue analytical method development and dietary exposure risk assessment of 345 pesticides in mango by LC-Q-TOF/MS - Xingqiang Wu; Jianxun Li; Jing Wei; Kaixuan Tong; Yujie Xie; Qiaoying Chang; Xiaoxuan Yu; Bei Li; Meiling Lu; Chunlin Fan; Hui Chen (Food Control, 2025)

Spatiotemporal changes of vegetation in the northern foothills of Qinling Mountains based on kNDVI considering climate time-lag effects and human activities - Lili Chen; Zhenhong Li; Chenglong Zhang; Xinxin Fu; Jiahao Ma; Meiling Zhou; Jianbing Peng (Environmental Research, 2025)

NIR-activated endoplasmic reticulum stress amplifier to regulate phagocytosis for macrophage-mediated cancer immunotherapy - Yaru Zhang; Wenyu Xie; Jiamin Luo; Rui Gao; Zhimin Gao; Xinyi Wang; Yongxin Huang; Chen Lin; Meiling Tan; Zhiyao Hou (Chemical Engineering Journal, 2025)

Correction to: Metanephric mesenchyme-derived Foxd1+ mesangial precursor cells alleviate mesangial proliferative glomerulonephritis - Meiling Jin; Zhong Yin; Kai Wei; Yuansheng Xie; Xueyuan Bai; Bo Fu; Zhe Feng; Qinggang Li; Xiangmei Chen (Journal of Molecular Medicine, 2025)

A Hypothetical Protein Fragment from Large Yellow Croaker (Larimichthys crocea) Demonstrates Significant Activity Against Both Bacterial and Parasite - Chunmei Yan; Meiling Chen; Hao Xu; Jian Jin; Xiande Liu; Zhiyong Wang; Dongling Zhang (Fishes, 2025)
Antimicrobial peptides (AMPs) are biocompatible and biodegradable, making them an attractive alternative to traditional antimicrobial agents and chemical preservatives. Here, a novel α-helix amphiphilic anionic AMP Lc149 was screened from a large yellow croaker (Larimichthys crocea) using a Bacillus subtilis expression system. Lc149 is a hypothesized protein fragment not annotated in the genome of a large yellow croaker. Both extracellular protein and recombinant Lc149 (rLc149) exhibited significant killing effects against Gram-negative Escherichia coli and Vibrio harveyi. Scanning and transmission electron microscopy revealed that rLc149 had the ability to disrupt bacterial cell membranes, causing irregular cell morphology, severe cell membrane damage, cytoplasm agglutination, and intracellular content leakage. Confocal laser scanning microscopy and flow cytometry further confirmed bacterial cell destruction and mortality rates of over 80%. Gel retardation assays and SDS-PAGE electrophoresis showed that rLc149 was unable to bind to bacterial DNA, but did reduce bacterial protein contents. Additionally, rLc149 maintained antibacterial activity against E. coli and V. harveyi upon exposure to temperatures of 25–100 °C, UV radiation time of 0–60 min, pH levels of 3–12, and different proteases. Biosafety assays revealed low hemolytic toxicity to erythrocytes of large yellow croaker, rabbit, and shrimp, and low cytotoxicity to large yellow croaker kidney cells and HEK 293T cells. More deeply, rLc149 also possessed significant killing activity against parasites. Therefore, rLc149 can be considered an antibacterial and antiparasitic drug in fisheries.

Impact of humidity variations at different distances from the lake surface on rhizosphere microbiota of Trifolium repens L - Jin Chen; Meiling Ping; Xiaowan Geng; Keqing Lin; Boyan Wang; Yuxin Zhai; Yizhen Meng; Xiaoyu Li (Physiological and Molecular Plant Pathology, 2025)

Microscale fluvial landscape evolution and its impacts on early human settlement at the Shangshan cultural site in the upper Qiantang region, eastern China - Wenjia Zhang; Zhou Lin; Guoping Zhang; Leping Jiang; Meiling Chen; Shengchao Zhou; Yuchen Zhang; Xiang Zhao (Geomorphology, 2025)

Estimation of winter wheat yield by assimilating MODIS LAI and VIC optimized soil moisture into the WOFOST model - Jing Zhang; Guijun Yang; Junhua Kang; Dongli Wu; Zhenhong Li; Weinan Chen; Meiling Gao; Yue Yang; Aohua Tang; Yang Meng; Zhihui Wang (European Journal of Agronomy, 2025)

Saikosaponins alleviate depression-like behaviors of chronic unpredictable mild stress exposed mice through ERK signaling pathway - Min Chen; Min Li; Liwei Ma; Huiling Hou; Meiling Tang; Qiang Li (Experimental Brain Research, 2025)

Thresholding Dolphin Whistles Based on Signal Correlation and Impulsive Noise Features Under Stationary Wavelet Transform - Xiang Zhou; Ru Wu; Wen Chen; Meiling Dai; Peibin Zhu; Xiaomei Xu (Journal of Marine Science and Engineering, 2025)
The time–frequency characteristics of dolphin whistle signals under diverse ecological conditions and during environmental changes are key research topics that focus on the adaptive and response mechanisms of dolphins to the marine environment. To enhance the quality and utilization of passive acoustic monitoring (PAM) recorded dolphin whistles, the challenges faced by current wavelet thresholding methods in achieving precise threshold denoising under low signal-to-noise ratio (SNR) are confronted. This paper presents a thresholding denoising method based on stationary wavelet transform (SWT), utilizing suppression impulsive and autocorrelation function (SI-ACF) to select precise thresholds. This method introduces a denoising metric ρ, based on the correlation of whistle signals, which facilitates precise threshold estimation under low SNR without requiring prior information. Additionally, it exploits the high amplitude and broadband characteristics of impulsive noise, and utilizes the multi-resolution information of the wavelet domain to remove impulsive noise through a multi-level sliding window approach. The SI-ACF method was validated using both simulated and real whistle datasets. Simulated signals were employed to evaluate the method’s denoising performance under three types of typical underwater noise. Real whistles were used to confirm its applicability in real scenarios. The test results show the SI-ACF method effectively eliminates noise, improves whistle signal spectrogram visualization, and enhances the accuracy of automated whistle detection, highlighting its potential for whistle signal preprocessing under low SNR.

Advanced treatment of coal to ethylene glycol industry wastewater by catalytic ozonation: Performance and mechanism - Yingying Dong; Lan Yang; Nan Zhang; Ningning Xiao; Yongxia Sun; Ye Yang; Meiling Liu; Zhiwen Chen; Jiangwei Wang; Wendong Wang (Journal of Water Process Engineering, 2025)

Facile solvothermal synthesis of ultrafine platinum nanowires on carbon nanotubes to enhance hydrogen evolution performance - Chang-An Zhou; Meiling Ran; Huixi Chen; Tingting Ma; Chunhui Wu; Hong Zhang; Lei Song; Chao Wang; Kui Ma; Hairong Yue (Fuel, 2025)

Melatonin treatment maintains the quality properties and storability of carambola fruit by modulating energy metabolism - Ting Hu; Shaojie Zheng; Qingqing Liu; Meiling Li; Jingyuan Chen; Huili Zhang; Mengshi Lin; Hetong Lin; Yihui Chen (Food Chemistry, 2025)

Birnessite enhanced Cr(III) oxidation during subsurface geochemical processes: Role of Mn(III)-induced nonphotochemical reactive oxygen species - Yuting Zhou; Chuling Guo; Yanping Deng; Yanjun Jiang; Meiling Yin; Kai Chen; Siyu Zhang; Guining Lu; Zhi Dang (Environmental Pollution, 2025)

A novel operational water quality mobile prediction system with LSTM-Seq2Seq model - Lizi Xie; Yanxin Zhao; Pan Fang; Meiling Cheng; Zhuo Chen; Yonggui Wang (Environmental Modelling & Software, 2025)

A lightweight fine-grained pelagic fish recognition algorithm based on object detection - Weiyu Ren; Dongfan Shi; Yifan Chen; Liming Song; Qingsong Hu; Meiling Wang (Aquaculture International, 2025)

Abnormal sensory processing cortex in insomnia disorder: a degree centrality study - Hui Wang; Haining Li; Ziyi Liu; Chiyin Li; Zhaoyao Luo; Wei Chen; Meiling Shang; Huiping Liu; Fatemeh Naderi Nejad; Yuanping Zhou; Ming Zhang; Yingxiang Sun (Brain Imaging and Behavior, 2025)

Effects of coexisting goethite or lepidocrocite on Fe(II)-induced ferrihydrite transformation pathways and Cd speciation - Meiling Yin; Xin Li; Chuling Guo; Qiaohui Zhong; Xiaofei Li; Lijuan Zeng; Yuting Zhou; Chen Yang; Zhi Dang (Science of The Total Environment, 2025)

Acrylamide drives amidase-mediated gut dysbiosis to aggravate colitis - Daotong Li; Yinghua Luo; Huimin Fan; Li Dong; Xiaoying Zhang; Yu Feng; Meiling Tian; Shuqing Zhang; Wenjing Chen; Lujia Zhang; Jianwei Gao; Xiangning Ma; et al. (Science Bulletin, 2025)

Improving the functional components and biological activities of navel orange juice through fermentation with an autochthonous strain Lactiplantibacillus paraplantarum M23 - Meiling Huang; Chunling Lai; Yan Liang; Qin Xiong; Chaoyun Chen; Zhiran Ju; Yueming Jiang; Jun Zhang (Food and Bioproducts Processing, 2025)

Longitudinal relationship between built environment and physical fitness in Chinese children and adolescents: Findings from the COHERENCE study - Jinghong Liang; Shan Huang; Wenwen Bao; Yingqi Pu; Meiling Liu; Xiuzhi Yang; Zhuowen Wu; Jiaqi Chen; Guanghui Dong; Yajun Chen (Building and Environment, 2025)

Structural modifications of berberine and the lipid-regulating effects of its derivatives - Yun Lu; Mengxuan Yin; Yuting Lai; Xinyi Ye; Meiling Chen; Yubo Li (Medicinal Chemistry Research, 2025)

Bacillus subtilis 2118 exhibits bactericidal activity due to an inserted fish cDNA library - Chunmei Yan; Meiling Chen; Jian Jin; Xiande Liu; Zhiyong Wang; Yongju Luo; Dongling Zhang (Aquaculture, 2024)

Dynamic planning of crowd evacuation path for metro station based on Dynamic Avoid Smoke A-Star algorithm - Songtao Zuo; Zhanli Mao; Chuangang Fan; Xin Chen; Meiling Gong; Jianxing Ren; Xiaoxiao Fan; Yongnan Guo (Tunnelling and Underground Space Technology, 2024)

Functionalization of cellulose by facile Dissolution-Regeneration in A novel CS2/DBU/DMSO solvent system for detection of metal ions and antibacterial - Yuyan Zheng; Zinan Li; Meiling Chen; Jiyang Zuo; Tao Yang; Wenhua Miao; Yadong Zhao; Fei Liu; Jinggang Wang; Jin Zhu (Chemical Engineering Journal, 2024)

Long Transients May be Temporary Visits of Concealed Alternative Stable States - Xudong Liu; Meiling Liu; Ruiqing Zhu; Changming Zhao; Ning Chen (Ecosystems, 2024)

Microbial inoculants using spent mushroom substrates as carriers improve soil multifunctionality and plant growth by changing soil microbial community structure - Hui Nie; Chong Li; Zhaohui Jia; Xuefei Cheng; Xin Liu; Qianqian Liu; Meiling Chen; Yong Ding; Jinchi Zhang (Journal of Environmental Management, 2024)

Genomic selection on ear height, plant height and grain yield in the primary testing stage of maize hybrids - Xinying Kong; Shuwen Ji; Yubo Liu; Xuecai Zhang; Meiling Liu; Chen Yue; Ruichen Yang; Cong Li; Xiaomei Dong; Ao Zhang; Yanye Ruan (Euphytica, 2024)

Postglacial ocean methane release from the northern South China Sea - Mengyuan Wang; Xinyi Chen; Yu Liao; Lina Qin; Meiling Man; Guodong Jia; Ming Su (Quaternary Science Reviews, 2024)

Integrated effect of aspect ratio and tree spacing on pedestrian thermal comfort of street canyon - Xiaoping Chen; Meng Han; Jinyu He; Hang Ma; Meiling Han; Yanhong Liu; Xiaogang Wu (International Journal of Biometeorology, 2024)

m6A-mediated HDAC9 upregulation promotes particulate matter-induced airway inflammation via epigenetic control of DUSP9-MAPK axis and acts as an inhaled nanotherapeutic target - Yingying Zeng; Xin Bai; Guiping Zhu; Mengchan Zhu; Wenjun Peng; Juan Song; Hui Cai; Ling Ye; Cuicui Chen; Yuanlin Song; Meiling Jin; Xue-Qing Zhang; et al. (Journal of Hazardous Materials, 2024)

Nanoarchitectonics of bamboo-based heterojunction photocatalyst for effective removal of organic pollutants - Xiaole Yan; Meiling Chen; Junning Wang; Zhaodong Wang; Ruiqi Xin; Dujuan Wu; Ye Song; Song Li; Wenkai Zhu; Chaohai Wang; Yanli Mao (Chemical Engineering Journal, 2024)

A Profile of Drug-Resistant Mutations in Mycobacterium tuberculosis Isolates from Guangdong Province, China - Chenchen Zhang; Zhuhua Wu; Xinchun Huang; Yuchuan Zhao; Qi Sun; Yanmei Chen; Huixin Guo; Qinghua Liao; Huizhong Wu; Xunxun Chen; Anqi Liang; Wenya Dong; et al. (Indian Journal of Microbiology, 2024)

Occupation patterns during the Shangshan in the upper Qiantang River Basin, eastern China: A geomorphic study based on GIS - Wenjia Zhang; Zhou Lin; Leping Jiang; Chao Ding; Meiling Chen; Shengchao Zhou; Xiang Zhao (Quaternary International, 2024)

Effects of microplastics on sedimentary greenhouse gas emissions and underlying microbiome-mediated mechanisms: A comparison of sediments from distinct altitudes - Meiling Yi; Jingnan Liu; Maosen Ma; Sibo Zhang; Xin Chen; Xinghui Xia; Yang Li (Journal of Hazardous Materials, 2024)

Acidic electrolyzed-oxidizing water treatment mitigated the disease progression in Phomopsis longanae Chi-infected longans by modulating ROS and membrane lipid metabolism - Meiling Li; Hetong Lin; Chao Wang; Yazhen Chen; Mengshi Lin; Yen-Con Hung; Yifen Lin; Zhongqi Fan; Hui Wang; Yihui Chen (Food Chemistry, 2024)

The influence of human activities on rainfall-runoff relationships at different time scales in the Minjiang River Basin - Kaili Geng; Xingwei Chen; Meiling Zheng; Yunpeng Gao; Zipeng Gu; Huaxia Yao (Theoretical and Applied Climatology, 2024)

Cellulose nanofibrils-stabilized food-grade Pickering emulsions: Clarifying surface charge's contribution and advancing stabilization mechanism understanding - Yadong Zhao; Feifan Zhang; Meiling Chen; Fei Liu; Bin Zheng; Wenhua Miao; Huimin Gao; Rusen Zhou (Food Hydrocolloids, 2024)

Elevated CO2 exacerbates the risk of methylmercury exposure in consuming aquatic products: Evidence from a complex paddy wetland ecosystem - Danni Wu; Lei Chen; Xueying Zong; Fan Jiang; Xiaojie Wang; Meiling Xu; Fuxun Ai; Wenchao Du; Ying Yin; Hongyan Guo (Environmental Pollution, 2024)

Subalpine peatland development since the Last Glacial Maximum in subtropical China: Predominantly controlled by monsoonal climate and local topography - Cong Chen; Kangyou Huang; Dehao Xie; Meiling Man; Yongjie Tang; Yuanfu Yue; Xiao Zhang; Zhuo Zheng; Rachid Cheddadi (CATENA, 2024)

Calcium polypeptide mitigates Cd toxicity in rice via reducing oxidative stress and regulating pectin modification - Hongbing Chen; Xiaojun Tang; Tiejun Wang; Weifang Liao; Zhixian Wu; Meiling Wu; Zhihao Song; Yadong Li; Pan Luo (Plant Cell Reports, 2024)

Histological and single-nucleus transcriptome analyses reveal the specialized functions of ligular sclerenchyma cells and key regulators of leaf angle in maize - Qibin Wang; Qiuyue Guo; Qingbiao Shi; Hengjia Yang; Meiling Liu; Yani Niu; Shuxuan Quan; Di Xu; Xiaofeng Chen; Laiyi Li; Wenchang Xu; Fanying Kong; et al. (Molecular Plant, 2024)

Correction to: Characteristics of splenic PD-1+ γδT cells in Plasmodium yoelii nigeriensis infection - Dianhui Chen; Feng Mo; Meiling Liu; Lin Liu; Junmin Xing; Wei Xiao; Yumei Gong; Shanni Tang; Zhengrong Tan; Guikuan Liang; Hongyan Xie; Jun Huang; et al. (Immunologic Research, 2024)

Characteristics of splenic PD-1+ γδT cells in Plasmodium yoelii nigeriensis infection - Dianhui Chen; Feng Mo; Meiling Liu; Lin Liu; Junmin Xing; Wei Xiao; Yumei Gong; Shanni Tang; Zhengrong Tan; Guikuan Liang; Hongyan Xie; Jun Huang; et al. (Immunologic Research, 2024)
Although the functions of programmed death-1 (PD-1) on αβ T cells have been extensively reported, a role for PD-1 in regulating γδT cell function is only beginning to emerge. Here, we investigated the phenotypic and functional characteristics of PD-1-expressing γδT cells, and the molecular mechanism was also explored in the Plasmodium yoelii nigeriensis ( P. yoelii NSM)-infected mice . Flow cytometry and single-cell RNA sequencing (scRNA-seq) were performed. An inverse agonist of RORα, SR3335, was used to investigate the role of RORα in regulating PD-1 + γδT cells. The results indicated that γδT cells continuously upregulated PD-1 expression during the infection period. Higher levels of CD94, IL-10, CX3CR1, and CD107a; and lower levels of CD25, CD69, and CD127 were found in PD-1 + γδT cells from infected mice than in PD-1 − γδT cells. Furthermore, GO enrichment analysis revealed that the marker genes in PD-1 + γδT cells were involved in autophagy and processes utilizing autophagic mechanisms. ScRNA-seq results showed that RORα was increased significantly in PD-1 + γδT cells. GSEA identified that RORα was mainly involved in the regulation of I-kappaB kinase/NF-κB signaling and the positive regulation of cytokine production. Consistent with this, PD-1-expressing γδT cells upregulated RORα following Plasmodium yoelii infection. Additionally, in vitro studies revealed that higher levels of p-p65 were found in PD-1 + γδT cells after treatment with a RORα selective synthetic inhibitor. Collectively, these data suggest that RORα-mediated attenuation of NF-κB signaling may be fundamental for PD-1-expressing γδT cells to modulate host immune responses in the spleen of Plasmodium yoelii nigeriensis –infected C57BL/6 mice, and it requires further investigation.

All-in-one treatment: Capture and immobilization of 137Cs by ultra-stable inorganic solid acid materials HMMoO6·nH2O (M = Ta, Nb) - Zhihua Chen; Shaoqing Jia; Haiyan Sun; Junhao Tang; Yanling Guo; Yuexin Yao; Tianyu Pan; Meiling Feng; Xiaoying Huang (Water Research, 2024)

Surface properties of schwertmannite with different sulfate contents and its effect on Cr(VI) adsorption - Chaoping Wang; Kai Chen; Meiling Yin; Yuting Zhou; Qinglin Zhuang; Qianqian Cao; Zhi Dang; Chuling Guo (Geochimica et Cosmochimica Acta, 2024)

The short-term effect of simulated acid rain and nitrogen deposition on the soil microbial functional profile targeting C, N, and P cycling - Chong Li; Yong Ding; Shuifeng Zhang; Meiling Chen; Yuhao Wang; Zhaohui Jia; Shilin Ma; Jinchi Zhang; Xin Liu (Applied Soil Ecology, 2024)

Microbial features with uranium pollution in artificial reservoir sediments at different depths under drought stress - Siyu Liu; Juan Liu; Jingye She; Zhenyu Xie; Lei Zhou; Qunwei Dai; Xing Zhang; Yuebing Wan; Meiling Yin; Xinjiao Dong; Min Zhao; Diyun Chen; et al. (Science of The Total Environment, 2024)

Evaluation of magnetic calcium silicate hydrate derived from halloysite clay for efficient phosphate capture - Debin Jiang; Xue Long; Meiling Xiang; Xiantian Gan; Qinghong Pu; Yu Chen; Ning Qi; Xiaoping Wang (Journal of Environmental Chemical Engineering, 2024)

MnO2 nanozyme with lanthanide-based radiosensitization for advanced radiotherapy by tumor microenvironment triggering STING pathway activation - Meiling Tan; Zhimin Gao; Xiaozhao Wang; Chen Lin; Yuchi Wan; Wenyu Xie; Wei Chen; Yaru Zhang; Zewei Quan; Zhiyao Hou (Chemical Engineering Journal, 2024)

Pt,P-codoped carbon nitride nanoenzymes for fluorescence and colorimetric dual-mode detection of cholesterol - Meiling Chen; Yang Yang; Qinhua Chen; Lina Tang; Junlin Liu; Yujie Sun; Qiming Liu; Yulin Zhang; Guo-jun Zhang; Shaowei Chen (Analytica Chimica Acta, 2024)

A novel method to advance the brGDGTs-based paleoclimate reconstruction applicable to different terrestrial environments - Liping Tian; Mengyuan Wang; Cong Chen; Xiao Zhang; Zhuo Zheng; Meiling Man; Kangyou Huang; Li Li; Guodong Jia (Quaternary Science Reviews, 2024)

Chemical features and biological functions of water-insoluble dietary fiber in plant-based foods - Meiling Tian; SolJu Pak; Chen Ma; Lingjun Ma; Kannan R. R. Rengasamy; Jianbo Xiao; Xiaosong Hu; Daotong Li; Fang Chen (Critical Reviews in Food Science and Nutrition, 2024)

Illuminated fulvic acid stimulates denitrification and As(III) immobilization in flooded paddy soils via an enhanced biophotoelectrochemical pathway - Yanqiong Zeng; Honghui Wang; Jiehua Hu; Jing Zhang; Feng Wang; Tongyu Wang; Qiqi Zhou; Randy A. Dahlgren; Meiling Gao; Hui Gao; Zheng Chen (Science of The Total Environment, 2024)

Calcium isotopic compositions of eclogite melts and negligible modification during reaction with lithospheric mantle - Zongqi Zou; Zaicong Wang; Xiao-Jun Wang; Yi-Gang Xu; Li-Hui Chen; Meiling Wang; Lanping Feng; Ming Li; Yongsheng Liu (Geochimica et Cosmochimica Acta, 2024)

A prototype galectin-1 (also known as galecin-2) from large yellow croaker (Larimichthys crocea): Molecular and function study - Xin Tang; Zhiqun Xiao; Meiling Chen; Jian Jin; Chunmei Yan; Xingcheng Zhu; Zhiyong Wang; Dongling Zhang (Fish & Shellfish Immunology, 2024)

Identification of QTLs associated with very-long chain fatty acid (VLCFA) content via linkage mapping and BSA-seq in peanut - Xiaomeng Xue; Jianguo Li; Jie Wu; Meiling Hu; Nian Liu; Liying Yan; Yuning Chen; Xin Wang; Yanping Kang; Zhihui Wang; Huifang Jiang; Yong Lei; et al. (Theoretical and Applied Genetics, 2024)

Evolution of sustainability and its driving characteristics in typical energy-rich counties in underdeveloped Northwest China - Honghua Li; Xingang Fan; Meiling Yang; Xueli Chen; Manman Zhao (Environment, Development and Sustainability, 2024)

The role of energy transport system in pericarp browning of harvested longan fruit - Meiling Li; Hetong Lin; Yazhen Chen; Yihui Chen; Yifen Lin; Zhongqi Fan; Hui Wang (Postharvest Biology and Technology, 2024)

In situ formation of fluorescence species for the detection of alkaline phosphatase and organophosphorus pesticide via the ascorbate oxidase mimetic activity of AgPd bimetallic nanoflowers - Luo Luo; Jing Liu; Yani Liu; Haoyu Chen; Youyu Zhang; Meiling Liu; Shouzhuo Yao (Food Chemistry, 2024)

A Fe-Ni-MOF-74@bamboo photothermal evaporator for efficient solar steam generation - Yiduo Chen; Dongxu Gu; Yujuan Zhao; Chaowei Zhang; Meiling Li; Qi Zhou; Yonghui Lin; Yaru Gong; Zhongmin Su; Weiting Yang (Desalination, 2024)

Amino-functionalized nanocellulose aerogels for the superior adsorption of CO2 and separation of CO2/CH4 mixture gas - Wenkai Zhu; Meiling Chen; Jieun Jang; Minsu Han; Yeonggyun Moon; Junghwan Kim; Jungmok You; Song Li; Teahoon Park; Jeonghun Kim (Carbohydrate Polymers, 2024)

Predicting and extracting thermal behavior rules of hydronic thermal barrier with interpretable ensemble learning in the heating season - Juanli Guo; Zhoupeng Wang; Yongyun Jin; Meiling Li; Qingwei Chen (Energy and Buildings, 2023)

Dual responsive cellulose-based fluorescent material fabricated in a CO2 switchable solvent for multifunctional applications - Yiting Xu; Xiaobo Yu; Meiling Chen; Yi Sun; Wei Zhang; Yajin Fang; Lanyun Fang; Haining Na; Fei Liu; Jin Zhu (Chemical Engineering Journal, 2023)

Decomplexation of Ni-EDTA enhanced by Fe(III) reduction in the Fenton reaction: Insight into the role of carbonyl groups - Meiling Chen; Lin Ding; Shijun Zhu; Xiuqin Xiong; Xinkai Yuan; Yanhua Peng; Liming Yang; Hui Shi; Penghui Shao; Xubiao Luo (Journal of Environmental Chemical Engineering, 2023)

Exposure to ambient air pollutants is associated with an increased incidence of hyperuricemia: A longitudinal cohort study among Chinese government employees - Lidan Duan; Muyang Zhang; Yuhan Cao; Yuwei Du; Meiling Chen; Rumeng Xue; Minxue Shen; Dan Luo; Shuiyuan Xiao; Yanying Duan (Environmental Research, 2023)

Aerogel-hydrogel biphase gels based on physically crosslinked β-lactoglobulin fibrils/polyvinyl alcohol for skin wound dressings: In vitro and in vivo characterization - Min Gong; Huanhuan Shi; Zuquan Hu; Fang Wang; Meiling Dong; Ronghua Lei; Zhu Zeng; Yun Wang; Jin Chen (Chemical Engineering Journal, 2023)

Study on optimization of shelter locations and evacuation routes of gas leakage accidents in chemical industrial park - Di Zhang; Zhanli Mao; Meiling Gong; Jianxing Ren; Songtao Zuo; Xin Chen (Process Safety and Environmental Protection, 2023)

Dose-response relationship of elements with blood lipids and the potential interaction: A cross-sectional study from four areas with different pollution levels in China - Shaoyi Chen; Muyang Zhang; Lidan Duan; Meiling Chen; Yuwei Du; Yuhan Cao; Zhijun Huang; Jia Zhao; Yanying Duan (Journal of Trace Elements in Medicine and Biology, 2023)

Savanna/rainforest dynamics and hydroclimate changes in northern boundary of tropical Asia over the past 150 kyrs - Cong Chen; Kangyou Huang; Zhuo Zheng; Yongqiang Zong; Peter Kershaw; Shixiong Yang; Liping Tian; Meiling Man; Sheng-Hua Li; Chris Brodie; Ning Wang; Xiao Zhang; et al. (Global and Planetary Change, 2023)

A new S-scheme heterojunction of 1D ZnGa2O4/ZnO nanofiber for efficient photocatalytic degradation of TC-HCl - Wenhui Chen; Tianxin Kang; Fenqi Du; Peipei Han; Meiling Gao; Peng Hu; Feng Teng; Haibo Fan (Environmental Research, 2023)

Insight into the molecular mechanism of phosphine toxicity provided by functional analysis of cytochrome b5 fatty acid desaturase and dihydrolipoamide dehydrogenase in the red flour beetle, Tribolium castaneum - Xu Shen; Meiling Che; Honglei Xu; Xinbo Zhuang; Erhu Chen; Peian Tang; Kangxu Wang (Pesticide Biochemistry and Physiology, 2023)

Oil occurrence state and quantity in alkaline lacustrine shale using a high-frequency NMR technique - Chenxi Zhang; Fujie Jiang; Tao Hu; Di Chen; Liliang Huang; Zhenxue Jiang; Xiaohao Wang; Zheyu Liu; Yuping Wu; Jiahao Lv; Renda Huang; Meiling Hu; et al. (Marine and Petroleum Geology, 2023)

High mechanical CuO@stainless steel mesh for continuous and durable separation of surfactant-stabilized viscous and light/heavy-mixed oily emulsions in liter-scale - Qing He; Meiling Guo; Juan Shu; Hua Hu; Hongwei Su; Guilong Yan; Zhenyu Li; Li Wang; Dong Xiang; Chunxia Zhao; Yuanpeng Wu; Wei Wang; et al. (Journal of Water Process Engineering, 2023)

Development and Characterization of Multifunctional Wound Dressing with the Property of Anti-bacteria and Angiogenesis - Xi He; Meiling Zhou; Xuemei Chen; Jing Wang; Xiaoli Zhao; Yanxia Zhu; Tao Liu (Probiotics and Antimicrobial Proteins, 2023)

Efficacy and safety of IL-23 inhibitors in the treatment of psoriatic arthritis: a meta-analysis based on randomized controlled trials - Xiaojing Huang; Haojie Shentu; Yujing He; Haijia Lai; Chen Xu; Meiling Chen; Haowei Zhu (Immunologic Research, 2023)
In recent years, the use of interleukin (IL) 23 inhibitors in the treatment of psoriatic arthritis (PsA) has been the subject of much research. By specifically binding to the p19 subunit of IL-23, IL-23 inhibitors block downstream signaling pathways and inhibit inflammatory responses. The objective of this study was to assess the clinical efficacy and safety of IL-23 inhibitors in the treatment of PsA. PubMed, Web of Science, Cochrane Library, and EMBASE databases were searched from the time of conception to June 2022 for randomized controlled trials (RCTs) investigating the use of IL-23 in PsA therapy. The main outcome of interest was the American College of Rheumatology 20 (ACR20) response rate at week 24. We included six RCTs (3 studies on guselkumab, 2 on risankizumab, and 1 on tildrakizumab) with a total of 2971 PsA patients in our meta-analysis. We found that the IL-23 inhibitor group showed a significantly higher ACR20 response rate compared to the placebo group (relative risk = 1.74, 95% confidence interval: 1.57–1.92; P < 0.001; I 2 = 40%). There was no statistical difference in the risk of adverse events ( P = 0.07) and serious adverse events ( P = 0.20) between the IL-23 inhibitor and placebo groups. Notably, the rate of elevated transaminases in the IL-23 inhibitor group was higher than the placebo group (relative risk = 1.69; 95%CI 1.29–2.23; P < 0.001; I 2 = 24%). In the treatment of PsA, IL-23 inhibitors significantly outperform placebo intervention while maintaining a favorable safety profile.

Ag2S QDs integration with MnO2 nanosheets for the sensitive detection of Cr (VI) via the redox reaction induced photoelectrochemical variation - Lili Zhao; Haoyu Chen; Ying Tang; Peipei Li; Xiaohua Zhu; Jingyi Liu; Meiling Liu; Youyu Zhang; Shouzhuo Yao (Analytica Chimica Acta, 2023)

The positive effects of mineral-solubilizing microbial inoculants on asymbiotic nitrogen fixation of abandoned mine soils are driven by keystone phylotype - Chong Li; Zhaohui Jia; Shuifeng Zhang; Tao Li; Shilin Ma; Xuefei Cheng; Meiling Chen; Hui Nie; Lu Zhai; Bo Zhang; Xin Liu; Jinchi Zhang; et al. (Science of The Total Environment, 2023)

Decomplexation of Ni-EDTA by thermally activated persulfate: Efficiency and mechanism - Xinkai Yuan; Wei Xiong; Yanhua Peng; Bo Li; Jianzhi Zhang; Meiling Chen; Xiuqin Xiong; Liming Yang; Hui Shi; Xubiao Luo; Penghui Shao (Journal of Water Process Engineering, 2023)

Characterisation of kapok fibre's biochar for arsenate adsorption removal from aqueous solution. - Kanfolo Franck Herve Yeo; Yingying Dong; Tongxuan Xue; Zhiwen Chen; Nan Zhang; Ye Yang; Liu Han; Meiling Liu; Ange Nsilani Kouediatouka; Hanse Pablick Patherny Lobo Mouguegue; Wendong Wang (Environmental Research, 2023)

Concomitant changes of lipid biomarker and water column mixing since mid-Holocene - Mengyuan Wang; Xinyi Chen; Lina Qin; Meiling Man; Ming Su; Guodong Jia (Chemical Geology, 2023)

Ambient air pollution and the health-related quality of life of older adults: Evidence from Shandong China - Jialong Tan; Nuo Chen; Jing Bai; Peizhe Yan; Xinyu Ma; Meiling Ren; Elizabeth Maitland; Stephen Nicholas; Wenjing Cheng; Xue Leng; Chen Chen; Jian Wang (Journal of Environmental Management, 2023)

SUMO and PIAS repress NF-κB activation in a basal chordate - Shenghui Chen; Xianan Fu; Ruihua Wang; Mingshi Li; Xinyu Yan; Zirui Yue; Shang-Wu Chen; Meiling Dong; Anlong Xu; Shengfeng Huang (Fish & Shellfish Immunology, 2023)

Response of microbial communities to nutrient removal in coastal sediment by using ecological concrete - Meiling Zhang; Jiannan Ji; Lemian Liu; Yisong Guo; Jianfeng Chen (Environmental Science and Pollution Research, 2023)

Regulatory role of myo-inositol in the ovarian development of female Chinese mitten crab (Eriocheir sinensis) - Xianyong Bu; Qincheng Huang; Ying Song; Changle Qi; Zhideng Lin; Xiaodan Wang; Meiling Zhang; Chuanjie Qin; Jian G. Qin; Liqiao Chen (Aquaculture, 2023)

Catalytic destruction of chlorobenzene over K-OMS-2: Inhibition of high toxic byproducts via phosphate modification - Yunpeng Long; Jiajia Liu; Meiling Chen; Renna Li; Xiaole Weng; Zhongbiao Wu (Journal of Environmental Sciences, 2023)

A Two-Stage Network Based on Transformer and Physical Model for Single Underwater Image Enhancement - Yuhao Zhang; Dujing Chen; Yanyan Zhang; Meiling Shen; Weiyu Zhao (Journal of Marine Science and Engineering, 2023)
The absorption and scattering properties of water can cause various distortions in underwater images, which limit the ability to investigate underwater resources. In this paper, we propose a two-stage network called WaterFormer to address this issue using deep learning and an underwater physical imaging model. The first stage of WaterFormer uses the Soft Reconstruction Network (SRN) to reconstruct underwater images based on the Jaffe–McGramery model, while the second stage uses the Hard Enhancement Network (HEN) to estimate the global residual between the original image and the reconstructed result to further enhance the images. To capture long dependencies between pixels, we designed the encoder and decoder of WaterFormer using the Transformer structure. Additionally, we propose the Locally Intended Multiple Layer Perceptron (LIMP) to help the network process local information more effectively, considering the significance of adjacent pixels in enhancing distorted underwater images. We also proposed the Channel-Wise Self-Attention module (CSA) to help the network learn more details of the distorted underwater images by considering the correlated and different distortions in RGB channels. To overcome the drawbacks of physical underwater image enhancement (UIE) methods, where extra errors are introduced when estimating multiple physical parameters separately, we proposed the Joint Parameter Estimation method (JPE). In this method, we integrated multiple parameters in the Jaffe–McGramery model into one joint parameter (JP) through a special mathematical transform, which allowed for physical reconstruction based on the joint parameter (JP). Our experimental results show that WaterFormer can effectively restore the color and texture details of underwater images in various underwater scenes with stable performance.

Astrochronology and carbon-isotope stratigraphy of the Fengcheng Formation, Junggar Basin: Terrestrial evidence for the Carboniferous-Permian Boundary - Renda Huang; Fujie Jiang; Di Chen; Ruoyuan Qiu; Tao Hu; Linhao Fang; Meiling Hu; Guanyun Wu; Chenxi Zhang; Jiahao Lv; Yuping Wu; Liliang Huang (Gondwana Research, 2023)

Acidic electrolyzed water treatment suppresses Phomopsis longanae Chi-induced the decreased storability and quality properties of fresh longans through modulating energy metabolism - Meiling Li; Qin Lin; Yazhen Chen; Yihui Chen; Mengshi Lin; Yen-Con Hung; Hetong Lin (Food Chemistry, 2023)

How do fish functional traits respond to dams at the global scale? - Meiling Chen; Yangyang Liang; Xinyu Cheng; Jun Wang; Liuyong Ding; Minrui Huang; Guojing Wang; Juan Tao; Chengzhi Ding (Hydrobiologia, 2023)

Impaired barrier integrity of endothelial cells induced by PEGylated black phosphorus nanosheets - Jiayan Chen; Weiwei Huan; Lijuan Mao; Meiling Huang; Yiqu Wu; Shulin Zhuang; Shixuan Cui (Science of The Total Environment, 2023)

Cellulose-based fluorescent materials fabricated in CO2 switchable solvent for freshness monitoring - Yi Sun; Wei Zhang; Shan Lu; Wenhua Miao; Meiling Chen; Fei Liu; Haining Na; Jin Zhu (Carbohydrate Polymers, 2023)

Vertical profile of PCDD/Fs in soil and sediment around an abandoned e-waste dismantling site - Xiaotong Su; Yucheng Zhang; Nora F. Y. Tam; Xiaolan Lao; Meiling Zhong; Qihang Wu; Yingheng Fei; Huifang Lei; Zihui Chen; Bixian Mai; Laiguo Chen (Journal of Soils and Sediments, 2023)

Simultaneous determination of 13 paralytic shellfish toxins and tetrodotoxin in marine shellfish by porous graphitic carbon solid-phase extraction and hydrophilic interaction chromatography-tandem mass spectrometry - Peizhen Li; Rongmao Lu; Jie Zhu; Qingqing Ke; Dingnan Wang; Yang Wang; Chen Zhang; Xinyue Lu; Miaolong Zhao; Zhang Wang; Lingling Pan; Meiling Zhang; et al. (Food Additives & Contaminants: Part A, 2023)

Research progress on antidiabetic activity of apigenin derivatives - Jingyi Jiang; Ting Tang; Yaling Peng; Meiling Liu; Qianwen Liu; Pengbing Mi; Zehua Yang; Hongfei Chen; Xing Zheng (Medicinal Chemistry Research, 2022)

Performance study of energy conversion system for ocean thermal profiler - Yanhu Chen; Bingzhe Chen; Meiling He; Luning Zhang; Qingchao Xia; Canjun Yang (Frontiers in Marine Science, 2022)
With the increasing scarcity of energy in the world, energy has become an important part of restricting the development and application of traditional ocean profilers. The method of converting ocean thermal energy (OTE) into electrical energy through an energy conversion system is a solution. The model establishment and performance analysis of the energy conversion system are the basis of the ocean thermal profiler (OTP) design. The model and performance are affected by the coupling of multiple parameters, especially rotational speed and pressure. In this study, a universal parameterized model for multi-parameter coupling was proposed. System performance analysis based on experiments including load current, speed, mechanical efficiency and total efficiency was presented. After model parameter identification, the error of mechanical efficiency was within 5%; the total efficiency error was less than 12.8%, and the maximum efficiency point error didn’t exceed 2.21%. The results indicated that the parameterized model was satisfactory for the engineering applications and could guide the design of OTP.

Comparative transcriptome analysis of global effect of ddh and lysE deletion on 4-hydroxyisoleucine production in Corynebacterium glutamicum - Rui Chen; Youhe Xiang; Xinping Yu; Meiling Zhang; Feng Shi (Systems Microbiology and Biomanufacturing, 2022)

Metatranscriptomic analysis of host response and vaginal microbiome of patients with severe COVID-19 - Meng Xiao; Bo Lu; Rui Ding; Xia Liu; Xian Wu; Yaqian Li; Xudong Liu; Lin Qiu; Zhibo Zhang; Jing Xie; Yu Chen; Dong Zhang; et al. (Science China Life Sciences, 2022)

Implications of spatial priority areas for hydrological ecosystem services through coupling hydrology model and Zonation model under different economic costs of water utilizations in northernmost of Japan - Min Fan; Manjiang Shi; Yunfeng Liu; Wen Chen; Yue Deng; Meiling Wang (Mitigation and Adaptation Strategies for Global Change, 2022)

Aggregate sizes regulate the microbial community patterns in sandy soil profile - Yifei Sun; Meiling Sun; Guowei Chen; Xin Chen; Baoguo Li; Gang Wang (Soil Ecology Letters, 2021)

Quality Study of the Preparation of Virgin Brown Sugar Powder by Vacuum Drying - Yuchao Dai; Mingxing Li; Meiling Li; Zhuolin Wang; Jie Lu; Yiyang Zhou; Wenping Meng; Shufang Chen; Qingtao Li (Sugar Tech, 2021)

Liver kinase B1 (LKB1) reduced inflammation and oxidative stress by regulating the AMPK/NLRP3 signaling pathway in LPS-induced lung injury - Yifeng Yue; Liwu Zong; Yongmin Chen; Nianhai Feng; Junxia Tang; Hongyu Xu; Meiling Zhao (Molecular & Cellular Toxicology, 2021)

The role of macrophage scavenger receptor 1 (Msr1) in prion pathogenesis - Bei Li; Meiling Chen; Adriano Aguzzi; Caihong Zhu (Journal of Molecular Medicine, 2021)
The progression of prion diseases is accompanied by the accumulation of prions in the brain. Ablation of microglia enhances prion accumulation and accelerates disease progression, suggesting that microglia play a neuroprotective role by clearing prions. However, the mechanisms underlying the phagocytosis and clearance of prion are largely unknown. The macrophage scavenger receptor 1 (Msr1) is an important phagocytic receptor expressed by microglia in the brain and is involved in the uptake and clearance of soluble amyloid-β. We therefore asked whether Msr1 might play a role in prion clearance and assessed the scavenger function of Msr1 in prion pathogenesis. We found that Msr1 expression was upregulated in prion-infected mouse brains. However, Msr1 deficiency did not change prion disease progression or lesion patterns. Prion deposition in Msr1 deficient mice was similar to their wild-type littermates. In addition, prion-induced neuroinflammation was not affected by Msr1 ablation. We conclude that Msr1 does not play a major role in prion pathogenesis. Key messages Msr1 expression is upregulated in prion-infected mouse brains at the terminal stage Msr1 deficiency does not affect prion disease progression Msr1 does not play a major role in prion clearance or prion pathogenesis Microglia-mediated phagocytosis and clearance of Aβ and prion may adopt distinct molecular pathways

Pigment profile and gene analysis revealed the reasons of petal color difference of crabapples - Ting Shen; Meiling Han; Qianrui Liu; Chen Yang; Jiaxin Meng; Houhua Li (Brazilian Journal of Botany, 2021)

Natural population re-sequencing detects the genetic basis of local adaptation to low temperature in a woody plant - Yanmin Hu; Xianjun Peng; Fenfen Wang; Peilin Chen; Meiling Zhao; Shihua Shen (Plant Molecular Biology, 2021)

Exendin-4 Reversed the PC12 Cell Damage Induced by circRNA CDR1as/miR-671/GSK3β Signaling Pathway - Hui Quan; Qiudan Chen; Kesheng Wang; Qinwan Wang; Meiling Lu; Yue Zhang; Sujing Qiang; Shaobo Xue; Lin Han; Huanhuan Zhu; Qiangyuan Fan; Meiyu Bao; et al. (Journal of Molecular Neuroscience, 2021)

The Effect of Composting on the Multiple Heavy Metals in the River Sediment Investigated by Multivariate Analysis - Yaoning Chen; Yanrong Chen; Yuanping Li; Yihuan Liu; Daoli Zhang; Yanxin Wu; Hui Li; Fangting Xu; Meiling Li (Water, Air, & Soil Pollution, 2021)

A tale of two cities: different urban heat mitigation efficacy with the same strategies - Meiling Gao; Fei Chen; Huanfeng Shen; Huifang Li (Theoretical and Applied Climatology, 2020)

Functional wastepaper-montmorillonite composite aerogel for Cd2+ adsorption - Yaoning Chen; Yihuan Liu; Yuanping Li; Li Zhao; Yanrong Chen; Hui Li; Yuqing Liu; Linshenzhang Li; Fangting Xu; Meiling Li (Environmental Science and Pollution Research, 2020)

Genetic basis of maize ear angle revealed by high-density single nucleotide polymorphism markers in four recombinant inbred line populations - Jingwei Lin; Shoukun Li; Gengyuan Liang; Meiling Liu; Taicheng Jin; Zhengwei Qu; Haoge Li; Shuisen Chen; Cong Li; Ao Zhang; Yanye Ruan; Zhenhai Cui (Euphytica, 2020)

Connectivity of fish assemblages along the mangrove-seagrass-coral reef continuum in Wenchang, China - Jianguo Du; Meiling Xie; Yuyu Wang; Zehao Chen; Wenhua Liu; Jianji Liao; Bin Chen (Acta Oceanologica Sinica, 2020)

The inhibition of miR-17-5p promotes cortical neuron neurite growth via STAT3/GAP-43 pathway - Liang Zhang; Zhijie Wang; Bo Li; Ziwei Xia; Xin Wang; Yucai Xiu; Zheng Zhang; Chuanjie Chen; Hong Song; Wenhua Li; Mei Yu; Meiling Zhang; et al. (Molecular Biology Reports, 2020)

Analysis of flavonoids and anthocyanin biosynthesis-related genes expression reveals the mechanism of petal color fading of Malus hupehensis (Rosaceae) - Meiling Han; Chen Yang; Jing Zhou; Jiabin Zhu; Jiaxin Meng; Ting Shen; Zhuanxia Xin; Houhua Li (Brazilian Journal of Botany, 2020)

Discovery and characterization of a stable lipase with preference toward long-chain fatty acids - Meiling Chen; Xiuzhen Gao; Wu Yang; Caili Sun; Junhuan Yang; Huaiyuan Zhang; Yuanda Song (Biotechnology Letters, 2020)

Analysis of organic carbon sources in tropical seagrass fish: a case study of the east coast of Hainan Province - Jianguo Du; Zehao Chen; Meiling Xie; Mingru Chen; Xinqing Zheng; Jianji Liao; Bin Chen (Marine Biology Research, 2019)

Metanephric mesenchyme-derived Foxd1+ mesangial precursor cells alleviate mesangial proliferative glomerulonephritis - Meiling Jin; Zhong Yin; Kai Wei; Yuansheng Xie; Xueyuan Bai; Bo Fu; Zhe Feng; Qinggang Li; Xiangmei Chen (Journal of Molecular Medicine, 2019)

Genome-wide identification of the pectate lyase-like (PLL) gene family and functional analysis of two PLL genes in rice - Yinzhen Zheng; Junjie Yan; Shuzhen Wang; Meiling Xu; Keke Huang; Guanglong Chen; Yi Ding (Molecular Genetics and Genomics, 2018)

Clonidine Protects Against Neurotoxicity Induced by Sevoflurane Through NF-κB Signaling Inhibition and Proinflammatory Cytokine Release in Rats - Lian Guo; Yi Yu; Naixing Xin; Jing Sun; Yong Chen; Meiling Yu (Journal of Molecular Neuroscience, 2018)

Gut Microbiota and its Modulation for Healthy Farming of Pacific White Shrimp Litopenaeus vannamei - Erchao Li; Chang Xu; Xiaodan Wang; Shifeng Wang; Qun Zhao; Meiling Zhang; Jian G. Qin; Liqiao Chen (Reviews in Fisheries Science & Aquaculture, 2018)

Combination of NAD+ and NADPH Offers Greater Neuroprotection in Ischemic Stroke Models by Relieving Metabolic Stress - Qiao Huang; Meiling Sun; Mei Li; Dingmei Zhang; Feng Han; Jun Chao Wu; Kohji Fukunaga; Zhong Chen; Zheng-Hong Qin (Molecular Neurobiology, 2018)

Resveratrol promotes the embryonic development of vitrified mouse oocytes after in vitro fertilization - Yang Wang; Meiling Zhang; Zi-Jiang Chen; Yanzhi Du (In Vitro Cellular & Developmental Biology - Animal, 2018)

Akt Inhibitor Perifosine Prevents Epileptogenesis in a Rat Model of Temporal Lobe Epilepsy - Feng Zhu; Jiejing Kai; Linglin Chen; Meiling Wu; Jingyin Dong; Qingmei Wang; Ling-Hui Zeng (Neuroscience Bulletin, 2018)

Characterization of a novel dsRNA mycovirus isolated from strain A105 of Rhizoctonia solani AG-1 IA - Meiling Zhang; Li Zheng; Chen Liu; Canwei Shu; Erxun Zhou (Archives of Virology, 2018)

Spatial and temporal variability in the net primary production of grassland in China and its relation to climate factors - Meiling Zhang; Rattan Lal; Youyi Zhao; Wenlan Jiang; Quangong Chen (Plant Ecology, 2017)

Accumulation of intact sulfur mustard in adipose tissue and toxicokinetics by chemical conversion and isotope-dilution liquid chromatography–tandem mass spectrometry - Bin Xu; Cheng Zong; Yajiao Zhang; Tianhong Zhang; Xiaoying Wang; Meiling Qi; Jianfeng Wu; Lei Guo; Peng Wang; Jia Chen; Qin Liu; Hua Xu; et al. (Archives of Toxicology, 2017)

Abnormal Functional Connectivity Density in Post-traumatic Stress Disorder - Youxue Zhang; Bing Xie; Heng Chen; Meiling Li; Feng Liu; Huafu Chen (Brain Topography, 2016)

Endogenous level of TIGAR in brain is associated with vulnerability of neurons to ischemic injury - Lijuan Cao; Jieyu Chen; Mei Li; Yuan-Yuan Qin; Meiling Sun; Rui Sheng; Feng Han; Guanghui Wang; Zheng-Hong Qin (Neuroscience Bulletin, 2015)

Integrating Genome-Wide Association Study and Brain Expression Data Highlights Cell Adhesion Molecules and Purine Metabolism in Alzheimer’s Disease - Zimin Xiang; Meiling Xu; Mingzhi Liao; Yongshuai Jiang; Qinghua Jiang; Rennan Feng; Liangcai Zhang; Guoda Ma; Guangyu Wang; Zugen Chen; Bin Zhao; Tiansheng Sun; et al. (Molecular Neurobiology, 2015)

Two distinct classes of protein related to GTB and RRM are critical in the sclerotial metamorphosis process of Rhizoctonia solani AG-1 IA - Canwei Shu; Jieling Chen; Si Sun; Meiling Zhang; Chenjiaozi Wang; Erxun Zhou (Functional & Integrative Genomics, 2015)

Characterization of Post-traumatic Stress Disorder Using Resting-State fMRI with a Multi-level Parametric Classification Approach - Feng Liu; Bing Xie; Yifeng Wang; Wenbin Guo; Jean-Paul Fouche; Zhiliang Long; Wenqin Wang; Heng Chen; Meiling Li; Xujun Duan; Jiang Zhang; Mingguo Qiu; et al. (Brain Topography, 2015)

In vitro evaluation of a mammary gland specific expression vector encoding recombinant human lysozyme for development of transgenic dairy goat embryos - Tao Gui; Meiling Zhang; Jianwen Chen; Yuanliang Zhang; Naru Zhou; Yu Zhang; Jia Tao; Liucai Sui; Yunsheng Li; Ya Liu; Xiaorong Zhang; Yunhai Zhang (Biotechnology Letters, 2012)

Structure and seasonal dynamics of bacterial communities in three urban rivers in China - Meiling Zhang; Na Yu; Liqiao Chen; Caihong Jiang; Yanjie Tao; Tian Zhang; Jun Chen; Di Xue (Aquatic Sciences, 2012)

Mining EST-Derived SSR Markers to Assess Genetic Diversity in Cassava (Manihot esculenta Crantz) - Meiling Zou; Zhiqiang Xia; Peng Ling; Yang Zhang; Xin Chen; Zusheng Wei; Weiping Bo; Wenquan Wang (Plant Molecular Biology Reporter, 2011)

Molecular characterization of the bacterial composition in two waste silk refining systems - Meiling Zhang; Xuexia Yang; Tian Zhang; Jun Chen; Di Xue (World Journal of Microbiology and Biotechnology, 2011)

Purification and Characterization of Two Novel Antimicrobial Peptides Subpeptin JM4-A and Subpeptin JM4-B Produced by Bacillus subtilis JM4 - Shimei Wu; Shifang Jia; Dandan Sun; Meiling Chen; Xiuzhu Chen; Jin Zhong; Liandong Huan (Current Microbiology, 2005)

Polymerase chain reaction analysis of laboratory generated bioaerosols - Zhai Junhui; Yang Ruifu; Che Fengxiang; Chen Meiling; Cui Hong (Aerobiologia, 1997)